Prevalence of childhood underweight and associated factors in Bangladesh: Evidence from Bangladesh demographic health survey data sets (2007, 2011, 2014 and 2017-18) - Hassan, Sakib AL; Islam, Tanjirul; Jui, Mahmuda Akter; Anni, Tayeeba Tabussum; Jafrin, Tanzina; Al-Mahde, Abdul Elah; Turzo, Noor A Alam; Tasfiya, Nuzhat; Islam, Md Amirul; Rahman, Md. Ashfikur (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
Background: In Bangladesh, the percentage of children found moderately and severely underweight were respectively 16.4% and 3.6% all over the country in 2018. This study aimed to determine the prevalence of and factors affecting childhood underweight<5 years old and identify socioeconomic inequalities contributing to childhood underweight in Bangladesh. Methods: Bangladesh Demographic Health Survey Data (2007, 2011, 2014 & 2017-2018) of 30,940 pairs were used for analysis. Chi-square tests were used to estimate the relationship between the independent variables chosen and underweight, binary logistic regression analysis was used to investigate potential risk factors, and decomposition analysis was conducted to assess inequality. Results: Binary logistic regression demonstrated that the children’s age, mother’s BMI, mother’s education level, father’s educational status, child delivery procedure, birth order of the child, recent diarrhea affectedness before the survey, sanitation, and wealth index were discovered to be essential variables affecting childhood underweight of children under 5 years old in Bangladesh.  Conclusion: The associated factors with underweight in this study should be considered when designing policies and programs, making it more effective to eradicate the underweight problem among children in Bangladesh.